SEEDBANK AND SEEDLING EMERGENCE CHARACTERISTICS OF WEEDS IN RICEFIELD SOILS OF THE MUDA GRANARY AREA IN NORTH-WEST PENINSULAR MALAYSIA - MAHFUZA BEGUM; ABDUL SHUKOR JURAIMI; SYED OMAR OMAR BIN SYED RASTAN; RAJAN AMARTALINGAM; AZMI BIN MAN (BIOTROPIA, 2006)
Tlie experiment was conducted in the glasshouse of UPM from March 2003 to June 2004 to determine the soil seedbank in the ricefields ot'Muda rice granary area in Peninsular Malaysia. Six soil cores of 5 cm in diameter and 10 cm depth were sampled from each of 24 fields. All samples from each individual field were bulked and placed in plastic trays of 38 x 25 x 10 cm. Soil was moistened as required and emergence of weed seedlings were recorded over period of one year. After one year, remaining seeds were separated, removed and identified. The total seed bank was estimated at 1136.48 million/ha of which 62.35% (708.60 million seedlings ha"1) germinated within 12 months and 37.65% (427.88 million seeds ha"1) remained ungerminated. Total of 20 taxa were recognized. Based on importance value (I.V.) the five most dominant species in terms of emerged seedling were Fimbristylis miliacea, Leplochloa chinensis, LitJwigia hyssopifolia, Cyperus difformii and C. iria. Of the remaining seeds the five dominant species with decreasing trend in ranking were F. miliacea, Scirpus lateriflonis, Monochoria vagina/is, L. hyssopifolia and L. chinensis. Ranking of total seed reserves (seedlings+ remaining seeds) were similar to emerged seedling indicating that emerged seedlings reflect the actual weed flora in the Muda area. Among the dominant species F. miliacea accounted for 58.07% of emerged seedlings, 79.31% of remaining seeds and 66.07% of total seed bank. Total seedling emergence of all species was higher in the first observation in April 2003 and cumulative seedling emergence showed no clear peaks.Â  Key words : Seedbank, seedling emergence, weeds, ricefield soils, Malaysia